STUDI TAFSIR AL-QUR’AN AL-KARIM KARYA MAHMUD YUNUS - Ririn; Muhith (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mahmud Yunus’s Tafsir Al-Qur’an Al-Karim is a significant contribution to the Nusantara Qur’anic exegetical tradition, addressing Indonesian readers’ needs in educational and da‘wah contexts. Nevertheless, its structure, method, and exegetical orientation require a more systematic mapping to clarify its scholarly contribution to Indonesian tafsir studies. This study aims to examine the work’s presentation characteristics, identify its dominant interpretive method and exegetical style, and assess its contribution to the development of Nusantara tafsir. Employing library research with a descriptive analytical approach, the study applies content analysis to the tafsir text and relevant supporting literature. The findings indicate that the tafsir adopts a concise and communicative explanatory style, strongly emphasizing educational and moral orientation, and providing practical interpretations for general readers. Its exegetical tendency reflects an adabi ijtima‘i (literary social) orientation, particularly in themes of ethics, worship, and social guidance. In conclusion, Mahmud Yunus’s tafsir serves as an accessible medium for strengthening Qur’anic literacy while enriching Nusantara tafsir through a pedagogical popular approach. Keywords: Mahmud Yunus; Nusantara tafsir; exegetical method.